Associations between per- and polyfluoroalkyl substances and dental caries in the US adults - Yun Chen; Yuting Huang; Zhuofan Yang; Lilei Zhu (Medicine, 2026)
Per- and polyfluoroalkyl substances (PFAS) are recognized environmental pollutants that have negative health effects. The association between PFAS and untreated root and coronal caries among adults is unknown. This study focused on the blood levels of various PFAS utilizing data from the National Health and Nutrition Examination Survey, which included a sample of 3340 individuals from the 2015 to 2020 cycles. The association between an individual’s PFAS and their risk of untreated root and coronal caries was examined in this study using multivariable logistic regression, which adjusted for factors to provide odds ratios. Reduced risks of untreated coronal caries were associated with higher blood concentrations of PFUnDA. WQS and quantile g-computation analysis yielded similar negative associations between PFAS mixtures and untreated coronal caries. There was no apparent pattern in the untreated root and coronal caries estimates throughout the PFAS mixture according to Bayesian kernel machine regression. An increase in PFAS mixture was linked to a lower risk of untreated root and coronal caries in females, according to the results of stratified analysis. This cross-sectional study suggests that associations between different individual PFAS and their mixes may be associated with untreated root and coronal caries. Given the cross-sectional design, causal relationships cannot be established.